Analisis Investasi Instrumen Obligasi - Thyophoida W.S. Panjaitan; Maria Widyastuti (BIP's JURNAL BISNIS PERSPEKTIF, 2012)
Companies are difficult to obtain bank loans in large amounts can obtain public funds by selling bonds. Because the relationship is directly intertwined with public investors, the loan amount can be larger with a cheaper interest rate than bank loans. For the investor, investing in bonds relatively more than the profitguarantee stock. Bond investors from income levels can be calculated relatively from awal.Obligasi generally provide a fixed interest rate for six the first month. Usually, in order to attract investor interest, fixed rate bonds are set higher than the bond launched on time deposito.Jika interest rates move down, then the isseur (corporate bonds) will suffer a loss. However, if the bonds are sold at the interest rate moves up, it could be that the effect was not offered investors received. For the investor risks losing the possibility of falling bond prices and bond investment opportunities outside if at that time the interest rate more higher than the interest rate bonds. Issuance of bonds, in particular, is much more difficult than stocks because bond issuers should consider carefully the movement of interest rates. For investors who are actively conducting transactions, the instrument can also bring in revenue bonds in the form of capital gains. The bondholders have the right to claim precedence over shareholders.